2017
DOI: 10.1037/ort0000173
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of school-based mental health playgroups for diagnosable and at-risk preschool children.

Abstract: Risk factors during preschool years, such as poverty and unattended social/emotional problems, are known to have a strong negative influence on children's later functioning. This study aimed to investigate the effectiveness of an on-site integrated school-based mental health services and consultation program for preschool children and their families. The sample consisted of 47 children and parents in 3 childcare centers who came from low-socioeconomic, urban backgrounds. Parents provided questionnaire data on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 65 publications
0
5
0
Order By: Relevance
“…This study demonstrated that two different group interventions implemented in an urban middle-school setting were successful in improving students' attachment security and reducing trauma symptoms in typically developing young adolescents from ethnically and socioeconomically minoritized backgrounds. Students benefit from school-based group intervention [68,69], but few studies have addressed the effectiveness of psychodynamically oriented school-based group interventions. The two interventions offer two different strategies for resolving trauma symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…This study demonstrated that two different group interventions implemented in an urban middle-school setting were successful in improving students' attachment security and reducing trauma symptoms in typically developing young adolescents from ethnically and socioeconomically minoritized backgrounds. Students benefit from school-based group intervention [68,69], but few studies have addressed the effectiveness of psychodynamically oriented school-based group interventions. The two interventions offer two different strategies for resolving trauma symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…While the majority of programs involved the parents as participants, the Responsive Early Childhood Curriculum, the Relationships for Growth and Learning Program and Early Head Start focused mainly on children ( Love et al, 2005 ; Landry et al, 2014 ; Bekar et al, 2017 ). These programs were targeted for toddlers at risk, due to individual or environmental risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…These programs were targeted for toddlers at risk, due to individual or environmental risk factors. Relationships for Growth and Learning used principles of play psychotherapy and was successful in that it enabled at-risk toddlers to catch-up to their peers in behavioral functioning ( Bekar et al, 2017 ). Early Head Start has been studied extensively with 3,000 families, with the research finding that it has positive impacts on children’s cognitive, behavioral, social and emotional functioning ( Love et al, 2005 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A facilitated family-centered model, such as EPIIC playgroups, provide these participatory opportunities for families not only to strengthen existing practices, decisions, and choices, but to learn new skills that directly relate to improving their child’s speech and language outcomes. Playgroup models have been used in a variety of contexts to support young children’s social-emotional skills (Kim et al, 2003; McCollum and Yates, 1994; McCollum et al, 2001), provide emotional support and social networks for refugee families (Jackson, 2006), and improve adaptive and behavioral skills of preschool children (Bekar et al, 2016). The EPIIC playgroups may provide benefits to children’s language skills while also providing the opportunity for parents to learn from one another and build a support network.…”
Section: Discussionmentioning
confidence: 99%